The canudo, the rapadura and the Parish:: rural festivities, an expression of heritage - Zanandréa, João Alberto (2025)
This study aims to understand the dimension of religious festivities or popularly known as chapel festivals in the municipalities of Machadinho and Maximiliano de Almeida (both in Rio Grande do Sul) through research with oral sources (interviews), documentary analysis, photographs, registry books, bibliographic research, visits to communities and chapels in an effort to respond and understand how the festivities are organized and continue to reproduce legacies, strengthening bonds between residents. The communities analyzed are Nossa Senhora do Monte Bérico, Linha Santo Antônio and Paróquia de São Sebastião in recent years (2022-2024), delimiting the space-time analyzed. The aim is to understand these festivities as historical processes, and that they are always linked to memory, to culture, enabling a way of understanding them as heritage and construction of collective identity.